LUMOS (LIGHTING AUTOMATIC POTATOS SEEDING), APLIKASI TEKNOLOGI PEMBENIHAN KENTANG BERBASIS PHOTOPHERIODIC - Amaliyah, Lia; Yatmo, Agung Heru; Pambudi, Akbar Setyo; Adilaksono, Indrawan Cahyo; Prasetya, Adriansyah Galih; Sugiarto, Yusron (Program Kreativitas Mahasiswa - Teknologi, 2014)
Sumberbrantas is an Agroindustrial village in Malang, East java, with the main commodities are potatoes. One of the farmer groups engaged in potatoes agricultural sector is Anjasmoro farmer groups III. This farmer groups special program is perform independently potato seeding in the greenhouse. But, this process is not optimal because of less lighting so the potatoes seed produced susceptible to disease and has a small size. Therefore, we innovate to apply LUMOS technology. LUMOS is an automatic lighting system based on photoperiodic. The purpose of this program is to determine a method of designing, manufacturing, Lumos application influences and effective way of socialization. Lumos has a size of 25m Ã 5m. there are 4 18 watt lights, there are control Box size 15cm Ã 21cm Ã 5cm, and can be used for 5 years. Making Lumos begins with assembly hardware, sensor calibration and software development. The results showed that potatoes produced has a diameter of 8.128 mm and a mass of 31.3 grams greater than before. This technology is able to produce potatoes seed up to 7,000 seeds/period and profit reached Rp 20,169,000.00 annually. It is expected that this technology into a technology demonstration for other potato farmers in Indonesia.Keywords: automatic lighting, potatoes seeding, photoperiodic